Analisis Ekonomi Politik Agraria dalam Akses Hutan di Wilayah Perhutani Melalui Program Perhutanan Sosial - Sartika Nur Shalati (Jurnal Perempuan, 2022)
The Social Forestry program in Perhutani-managed forest areas aims to improve the welfare of the community through jointmanagement and promote sustainability. The program uses the Partnership Cooperation (Kulin KK) scheme, which is regulated by theMinister of Environment and Forestry Regulation No. P 83 of 2016. However, this program has become a new conflict zone as variousactors are competing to dominate forest use. Women, who have allocated more time and energy to the agricultural sector, now havefew opportunities to be involved in forest management because of gender biases within the governance and implementation of theSocial Forestry program. Women also have to compete with various parties in order to participate in forest management includingPerhutani and the Forest Village Community Institution (Lembaga Masyarakat Desa Hutan—LMDH), the party authorised to manageforest utilization programs.